Exploring the connection between pet attachment and owner mental health: The roles of owner-pet compatibility, perceived pet welfare, and behavioral issues - Roxanne D. Hawkins; Annalyse Ellis; Charlotte Robinson (PLoS ONE, 2025)
Research exploring the connection between pet ownership and mental health has expanded substantially in recent years, yet scientific evidence remains inconclusive. Existing studies have oversimplified this relationship by focusing primarily on pet ownership itself, without accounting for crucial factors such as species of the pet, or important relationship dynamics such as owner-pet attachment orientations. This study sought to investigate whether the relationship between owner-pet attachment and owner mental health could be better understood through the lens of owner-perceived pet compatibility, perceived pet welfare, and pet behavioral issues. These under researched aspects are believed to play crucial roles in shaping owner-pet relationships and owner mental well-being. This study surveyed emerging adults (ages 18–26) who owned dogs and/or cats from the United Kingdom (N = 600) who self-identified as experiencing difficulties with anxiety and/or low mood, of whom some reported clinical diagnoses. Our findings revealed that dog owners exhibited more secure pet attachments than cat owners. Anxious attachment was associated with poorer mental health among dog owners, while avoidant attachment was associated with better mental health in both dog and cat owners. Insecure attachment related to poorer perceived pet quality of life, increased reports of pet behavioral problems, and poorer owner-pet compatibility, regardless of pet species. Additionally, poorer welfare and more behavioral problems were associated with poorer mental health for dog owners; these findings were not replicated for cat owners. Notably, a dog’s mental state (such as appearing depressed), as well as fear and anxiety, mediated the relationship between owner-pet attachment and owner mental health. Owner-dog compatibility, particularly in the affection domain, positively mediated the relationship between anxious attachment and poorer mental health, while negatively mediating the relationship between avoidant attachment and better mental health. These findings suggest that a simplistic view of pet ownership fails to capture the complexity of the factors that shape the mental health of pet owners and underscores the need to consider important owner-pet factors to fully understand how the human-pet relationship can impact the well-being of both people and their pets.